The in situ synthesis of conductive polyaniline patterns using micro-reactive inkjet printing. Issue 8 (11th February 2019) - Teo, Mei Ying; Stuart, Logan; Devaraj, Harish; Liu, Cody Yang; Aw, Kean C.; Stringer, Jonathan
Abstract : The micro-reactive inkjet printing technique and the patterned conductive PANI on a glass substrate using this printing method. Abstract : We have fabricated polyaniline (PANI) on glass substrates using in-air coalescence of two reactive inks, also known as the micro-reactive inkjet printing (MRIJP) technique, that would otherwise be challenging or impossible to create using conventional fabrication approaches.